Cenário televisivo: linguagens multiplas fragmentadas - Cardoso, João Batista Freitas (2006)
This study considers a semiotic system as something constituted by different codifications that act simultaneously; a television program is a text which involves some systems, among them scenography; and the scene is one of its elements. The general objective of the present work is to verify how the scene can participate of the televising text as a signification element. Analyzing the specificities of different types of televising scenes, this thesis has as a specific objective: to verify how the scene intervenes with texts of different types of programs, and how it relates to the context, and the other elements of the scene; to identify, in the analyzed programs, how the scene acts with bigger communicative intensity, objectifying to cause definitive interpreters; to indicate, in the television, the characteristics of the scene, how it relates to its structure and to its style, in some of its main genres; to suggest forms of use of the scene as significant element inside of some types of television programs. In order to reach the objectives, a bibliographical research was made, focusing scenography in the theater, television genres, scenographic topologies in the television, as well as a bibliographical survey of the instruments supplied by the peircean semiotics and the theories of gestalt. The observation of scene s space configurations, in the different television genres, was carried through a collection of national videographic material